2022
DOI: 10.1590/1806-9282.20220812
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of tumor necrosis in non-muscle invasive bladder cancer

Abstract: OBJECTIVE:We aimed to investigate the impact of tumor necrosis in non-muscle invasive bladder cancer on patients' recurrence and progression rates and survival outcomes. METHODS: This study was conducted retrospectively in a single tertiary center in Turkey. Medical records of patients who underwent transurethral resection of the bladder tumor between January 2016 and January 2021 were reviewed. Patients with pTa and pT1 non-muscle invasive bladder cancer who had undergone complete resection were included in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Second, the conclusion of this study cannot be considered definitive regarding the impact of tumor necrosis on the prognosis of non-muscle-invasive bladder cancer. While this study suggests that tumor necrosis was associated with cancer progression (p<0.001), as shown in Table 1, a subsequently more rigorous analysis using multivariate Cox regression has shown that there is no association between tumor necrosis and the recurrence (p>0.05) and progression (p>0.05) in patients with non-muscle-invasive bladder cancer, as described in Table 2 of this study 1 . Statistically, the evidence level of multivariate Cox regression analysis is higher than that of Kaplan-Meier analysis, because Cox regression analysis takes into account the influence of all confounding factors (such as age, gender, tumor number, and tumor size) while Kaplan-Meier analysis does not.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Second, the conclusion of this study cannot be considered definitive regarding the impact of tumor necrosis on the prognosis of non-muscle-invasive bladder cancer. While this study suggests that tumor necrosis was associated with cancer progression (p<0.001), as shown in Table 1, a subsequently more rigorous analysis using multivariate Cox regression has shown that there is no association between tumor necrosis and the recurrence (p>0.05) and progression (p>0.05) in patients with non-muscle-invasive bladder cancer, as described in Table 2 of this study 1 . Statistically, the evidence level of multivariate Cox regression analysis is higher than that of Kaplan-Meier analysis, because Cox regression analysis takes into account the influence of all confounding factors (such as age, gender, tumor number, and tumor size) while Kaplan-Meier analysis does not.…”
mentioning
confidence: 56%
“…These findings suggest that BMI should be taken into account when assessing the risk of bladder cancer recurrence and developing personalized treatment plans for survivors with bladder cancer. Therefore, the absence of BMI data in this study 1 limits the ability to draw comprehensive conclusions about the prognostic impact of tumor necrosis in patients with non-muscle-invasive bladder cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation